2021
DOI: 10.1111/1752-1688.12916
|View full text |Cite
|
Sign up to set email alerts
|

Extent and Causes of Chesapeake Bay Warming

Abstract: Coastal environments such as the Chesapeake Bay have long been impacted by eutrophication stressors resulting from human activities, and these impacts are now being compounded by global warming trends. However, there are few studies documenting long‐term estuarine temperature change and the relative contributions of rivers, the atmosphere, and the ocean. In this study, Chesapeake Bay warming, since 1985, is quantified using a combination of cruise observations and model outputs, and the relative contributions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 103 publications
0
43
0
1
Order By: Relevance
“…Three-hourly surface atmospheric fields with a horizontal resolution of 0.25° (winds, downward long-wave radiation, net short-wave radiation, precipitation, dewpoint temperature, air temperature and pressure) are obtained from ERA5 and interpolated to a 0.2° grid to create atmospheric forcing files for ChesROMS-ECB between 1979 and 2019. The ERA5 forcing was found to better represent interannual atmospheric temperature variability and long-term trends in the Chesapeake Bay region (Hinson et al, 2021) compared to earlier studies (Feng et al, 2015) using the North American Regional Reanalysis (Mesinger et al, 2006 (Moyer & Blomquist, 2020) are combined with USGS discharge (Bever et al, 2021). Riverine organic carbon concentrations are derived from the CBPWM organic nitrogen concentrations and fixed carbon-to-nitrogen ratios from Hopkinson et al (1998) (Garcia & Gordon, 1992).…”
Section: Model Forcingmentioning
confidence: 96%
See 1 more Smart Citation
“…Three-hourly surface atmospheric fields with a horizontal resolution of 0.25° (winds, downward long-wave radiation, net short-wave radiation, precipitation, dewpoint temperature, air temperature and pressure) are obtained from ERA5 and interpolated to a 0.2° grid to create atmospheric forcing files for ChesROMS-ECB between 1979 and 2019. The ERA5 forcing was found to better represent interannual atmospheric temperature variability and long-term trends in the Chesapeake Bay region (Hinson et al, 2021) compared to earlier studies (Feng et al, 2015) using the North American Regional Reanalysis (Mesinger et al, 2006 (Moyer & Blomquist, 2020) are combined with USGS discharge (Bever et al, 2021). Riverine organic carbon concentrations are derived from the CBPWM organic nitrogen concentrations and fixed carbon-to-nitrogen ratios from Hopkinson et al (1998) (Garcia & Gordon, 1992).…”
Section: Model Forcingmentioning
confidence: 96%
“…Model skill was assessed by comparing model results from Ref 2015 to observations along the main stem of the Chesapeake Bay. Since modeled temperature and salinity have been extensively evaluated with WQMP data as shown in Feng et al (2015) and Hinson et al (2021) and nitrogen concentrations have been evaluated in Da et al (2018), this study focuses on the evaluation of the carbonate system. Because of the large uncertainties associated with electrode pH data from the WQMP, recent carbonate system data from the 18 main stem stations (Figure 1) from Friedman et al ( 2020) are used here for model evaluation.…”
Section: Model Skill Assessment and Decadal Trend Calculationmentioning
confidence: 99%
“…A number of studies addressing temperature variability in the CB (Preston, 2004;Najjar et al, 2010;Ding and Elmore, 2015;Hinson et al, 2021) have consistently identified a continuous warming trend throughout the bay. In order to evaluate the role of longterm trends in SST vs. internal variability in affecting trends in MHW characteristics, we calculated the trend attributional ratio (TAR) following Marin et al (2021):…”
Section: Trend Attributional Ratiomentioning
confidence: 99%
“…Furthermore, estuaries serve as nursery habitats for a number of marine species and support major economic activities including aquaculture, fishing and tourism, providing several ecosystem services and benefits to our society. While warming trends have been detected in a number of estuaries across the globe (e.g., Ashizawa and Cole, 1994;Najjar et al, 2010;Seekell and Pace, 2011;Ding and Elmore, 2015;Oczkowski et al, 2015;Hinson et al, 2021), little is still known about extreme events in these environments, such as MHWs, including their basic characteristics, trends, how they may be connected to MHWs in the adjacent coastal ocean, and how they may respond to large scale climate variability. Nevertheless, few estuaries around the globe have long term temperature records available with appropriate temporal resolution and spatial coverage that allows the characterization of MHWs and their time evolution in these environments.…”
Section: Introductionmentioning
confidence: 99%
“…For some species, the extent of suitable seasonal habitat increased since 2000 (summer and fall habitats for juvenile weakfish, and spring and summer habitats for bay anchovy), whereas for other species, extents varied annually with no clear trend. None of the species examined were at the southern limit of their geographic range, and as waters of the Chesapeake Bay continue to warm (Hinson et al, 2021), we expect that suitable habitat extent may increase for species with broad thermal tolerances such as spot, weakfish, and bay anchovy. Other climate-related effects predicted for the region include increased precipitation and sea-level rise, both of which may alter salinity and salinity stratification.…”
Section: Discussionmentioning
confidence: 99%